2022
DOI: 10.1111/cts.13246
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a blockchain‐based dynamic consent platform (METORY) in a decentralized and multicenter clinical trial using virtual drugs

Abstract: Blockchain is a novel data architecture characterized by a chronological sequence of blocks in a decentralized manner. We aimed to evaluate the real-world feasibility of a blockchain-based dynamic consent platform (METORY) in a decentralized and multicenter trial. The study consisted of three visits (i.e., screening and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…Conveying proper understanding and ensuring security to the study participants are both crucial elements in eConsent. The results of the clinical trial revealed that informed consent that subjects gave did not always mean accurate understanding of the contents (25). The results were contradictory to the subjective feeling of understanding ("The app adequately acknowledged and provided information to let me know the progress of my action.")…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Conveying proper understanding and ensuring security to the study participants are both crucial elements in eConsent. The results of the clinical trial revealed that informed consent that subjects gave did not always mean accurate understanding of the contents (25). The results were contradictory to the subjective feeling of understanding ("The app adequately acknowledged and provided information to let me know the progress of my action.")…”
Section: Discussionmentioning
confidence: 88%
“…The final platform was implemented in an actual decentralized and multicenter clinical trial using virtual drugs (ClinicalTrials.gov identifier: NCT05047016) (25). The study consisted of 2-week visits and home-based procedures.…”
Section: User Experience In the Multicenter Clinical Trialmentioning
confidence: 99%
“…In addition, dynamic consent problems have been highlighted, including data readability and accessibility [126]. The authors of [127] constructed a blockchain‐based architecture for dynamic consent and tested its real‐world viability by using virtual drugs in a decentralized, multicentre clinical trial. Throughout the research, two major and three minor protocol adjustments were planned to imitate real‐world study conditions.…”
Section: Current Micro Applications In Clinical Trialsmentioning
confidence: 99%
“…12 In a previous study, we developed a blockchain-based electronic consent application named METORY and evaluated the application in a DCT scenario. 15,19 We integrated an electronic diary module into METORY to manage DCT procedures in a single application. The application can keep logs for the study procedures, and investigators can analyze the adherence to study procedures with the log.…”
Section: Introductionmentioning
confidence: 99%
“…Such minimal restrictions can enable the analysis of real-world behaviors of the participants and were used to evaluate the participants' understanding of informed consent. 15 To investigate the feasibility of DCT, we conducted a pilot clinical trial in participants with functional constipation symptoms. We designed a full DCT with "lowrisk" alternatives (e.g., drug to dietary supplements and patients to participants with mild symptoms) to evaluate practical feasibility while reducing risks to participants.…”
Section: Introductionmentioning
confidence: 99%